Search for b → u transitions in B± → [K-+π±π0]DK± decays - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We present a study of the decays B±→DK± with D mesons reconstructed in the K+π−π0 or K−π+π0 final states, where D indicates a D0 or a ¯¯¯D0 meson. Using a sample of 474×106 B¯¯¯B pairs collected with the BABAR detector at the PEP-II asymmetric-energy e+e− collider at SLAC, we measure the ratios R±≡Γ(B±→[K∓π±π0]DK±)Γ(B±→[K±π∓π0]DK±). We obtain R+=(5+12−10(stat)+2−4(syst))×10−3 and R−=(12+12−10(stat)+3−5(syst))×10−3, from which we extract the upper limits at 90% probability: R+<23×10−3 and R−<29×10−3. Using these measurements, we obtain an upper limit for the ratio rB of the magnitudes of the b→u and b→c amplitudes rB<0.13 at 90% probability.